The Impact of Human Resource Innovation and Creativity on the Marketing Effectiveness of MSMEs in the Tourism Sector in Indonesia - Astri Wulandari; Riska Aprilina; Bethani Suryawardani (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The tourism sector is one of the mainstays of Indonesia's economy. Micro, small, and medium enterprises (MSMEs) dominate both income generation and employment in this sector, contributing significantly to regional development. However, most tourism MSMEs still adopt conventional marketing methods, thus reducing their competitiveness in an increasingly digital and dynamic market environment. Objective: This study examines the impact of human resource (HR) innovation and HR creativity on the marketing effectiveness of tourism MSMEs in Indonesia. Methods: A quantitative cross-sectional survey of 300 MSME owners and managers across major tourism destinations—Bali, Lombok, and Yogyakarta—was carried out. Data were collected through a structured survey questionnaire and analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. Results: HR Innovation (Mean = 4.09) and HR Creativity (Mean = 4.23) received high scores but showed no significant relationship with marketing effectiveness (r ≈ −0.03; p > 0.05; R² = 0.002), indicating a very weak predictive model. This finding contradicts previous studies that found positive innovation–performance relationships. Conclusion: HR innovation and HR creativity are not significant predictors of marketing effectiveness. Organizational leadership, culture, and technological support are the key structural and systemic factors. Theoretical Contributions: This study highlights the need for an integrated HR development approach and theoretically contributes by demonstrating that creative resources require systemic mechanisms to translate into measurable marketing outcomes.